Digital Marketing Technologies - Aghazadeh, Hashem; Khoshnevis, Mozhde (Springer Nature Singapore, 2024)
This book argues that digital marketing should benefit from emerging technologies to result in sustainable competitive values for businesses in both the digital and physical worlds. It not only explores digital marketing fundamentals, analysis, strategy, practices, and implementation but also explains the applications and relationships of marketing technologies (martechs) with digital marketing; as well as offers several real cases of practicing marketing technologies. It carefully describes how modern businesses offer their value propositions both digitally and physically applying emerging technologies specifically marketing technologies (martechs) and how consumers are using these new technologies particularly artificial intelligence (ChatGPT/ OpenAI). It investigates why consumers are so intrigued and interested in digital relationships, interaction, and shopping experiences. It critically examines and argues that digital marketing has become popular among businesses as they are attempting to serve their customers better by taking advantage of using digital marketing technologies (marketchs)